The oil curse how petroleum wealth shapes the development of nations - Ross, Michael Lewin 1961- (Princeton University Press, 2012)
The Oil Curse shows why oil wealth typically creates less economic growth than it should; why it produces jobs for men but not women; and why it creates more problems in poor states than in rich ones. It also warns that the global thirst for petroleum is causing companies to drill in increasingly poor nations, which could further spread the oil curse.